Effect of salinity on wild pepper populations from Northwest Mexico: Effect of salinity on wild pepper populations from Northwest Mexico - Osuna Rodríguez, José Manuel; Hernández Verdugo, Sergio; Pacheco Olvera, Antonio; Osuna Enciso, Tomás; Parra Terraza, Saúl; Romero Higareda, César Enrique (Ecosistemas y Recursos Agropecuarios, 2024)
Salinity is a problem in agricultural areas by compromising the growth of crops. Modern pepper varieties are poorly adapted to this condition; therefore, the search for variability in wild pepper plants would help to create improved varieties. The objective was to determine the effects of salinity and the distribution of phenotypic variation between populations, between and within families, and to estimate the proportion of this phenotypic variation that has a genetic basis. Three treatments (0, 25 and 50 mM NaCl) were tested in six wild pepper populations from Northwestern Mexico. Significant differences were observed between treatments for all traits. Salinity reduced all traits except leaf thickness; was higher with 50 mM, root dry matter (45.2%), leaves (38.7%), leaf area (37.6%), total biomass (33.7%) being the most sensitive traits. The greatest phenotypic variation was distributed within families. The highest coefficient of variation was in root dry weight (40%). The populations maintained variation in all traits except plant height; Presa Oviachic was superior in dry weight of plant, root, stem and leaves, leaf area, number of leaves and stem diameter; Mazocahui in leaf thickness; Yecorato and Lo de Vega in SPAD readings. NaCl levels influenced the phenotypic expression of the studied traits. The variability detected in the populations is promising to begin a domestication process in wild pepper.